You are on page 1of 2

CÁLCULO DE LÍMITES

1) lim( 3 x 2 − 6 x + 1) 2) lim ( x 2 − 2 x + 1) 3) lim ( − 3x 3 + x )


x →1 x →∞ x →−∞

x 2 − ( a + 1) x + a x2 + x − 2  1
+
1 
4) lim 5) lim 6) lim  
x →a x2 − a2 x →1 x 2 − 2 x + 1 x →∞
 x +2 x −2
x2 + x −2 1 x4
7) lim 2 8) lim 9) lim
x →−1 x − 2 x +1 x →∞ x − 4x + 4
2 x →∞ − 2 x 4 + 3 x 3 − 6

x 2 − 6x + 9 x 2 − 25 x3 − 2x 2 + x
10) lim 11) lim 2 12) lim
x →0 x2 x →5 x − 5 x x →∞ 2x 2 − 6x
x4 − x2 − 3x 5 + x 2 x− a
13) lim 14) lim 15) lim
x →∞ x 5 + 1 x →−∞ 2 x 2 −1 x →a x −a

16) lim
x →0
3+x − 3
x
17) lim
x →5
( 3
x2 + 2 − x ) 18) lim
x →∞
x +1 − x + 2
x
  x +1 −1
2
x +1
2
19) lim  x + x+ x − x 20) lim 21) lim
x →∞
  x →∞
x +2 −4
2 x →−
∞ x +1
1
2 x +1 − 2 x −1
22)  x −1 
lim  
x −3
23) lim  x− x − x+ x
 24) lim
x →∞  
 2 x −4 
x →3+ x →∞ x +1 − x −1

25) lim
x →∞
( x( x +1 − x −1 )) 26) lim
x→∞
( (
x 3 + 1 2 x 5 − 2 x − 2 x 5 + 3x ))
  x −1  x 2 − 6 x − ( x − 3) x 3 − 6x 2 + 5x
27) lim  x −1  28) lim 29) lim
x →∞   x +1 
   x →∞
x + 3 − x 2 + 6x x →1 x 4 − x 3 + x −1

30) lim
( x +1) 3 31) lim
x 3 + 5 x 2 + 3x − 9
32) lim
x 4 − 2x3 + x − 2
x →−3 ( x + 3) 4 x →−3 x 3 + 7 x 2 + 15 x + 9 x →2 x 3 + 4 x 2 − 11 x − 2
x 4 + 4 x 3 + 5x 2 + 4 x + 4 x 4 − 6 x 2 + 8x − 3  x −2 x2 − 4 
33) lim 34) lim 4 35) lim  − 
x →2  x 2 − 4 x − 2 
x →−2 x 4 + 4x3 + 4x 2 x →1 x − 2 x 3 + 2 x − 1 
x +2 x +2 x +2
36) lim + 37) lim 38) xlim
x →−3 x + 3 −1 x →0 x + 3 −1 →−2 x + 3 −1
x +2 x +2 x−x
39) lim 40) xlim 41) lim
x →∞ x + 3 −1 →−∞ x + 3 −1 x→ 1 2x
x−x x−x x−x
42) lim 43) lim 44) lim
x →−1 2x x →0 2x x →∞ 2x
x−x x 2 −1 x 2 −1
45) lim lim
46) x →0 2 47) lim
x →−
∞ 2x x − 2 x −1 −1 x →1 x 2
− 2 x −1 −1
x 2 −1 sen x tg x sen x
48) lim 49) lim 50) lim 51) lim
x →∞ x 2 − 2 x −1 −1 x →0 x x →0 x x →0 tg x
sen x −sen a cos ( a + h ) − cos a cos 7 x −cos 3 x
52) lim 53) lim 54) lim
x →a x −a h →0 h x →0 x2
1 − cos x  π   π  sen 6 x
55) lim 56) lim sen  2  57) lim sen  2  58) lim
x →0 x2 x →1
 x −1  x →∞
 x −1  x →π 2 x
sen 6 x sen x sen ( x − 2 ) tg 5 x
59) lim 60) lim 61) lim 2 62) lim
x →0 x x →π π − x x →2 x − 5 x + 6 x →0 7x
lim tg
 x 2 − 3x + 2 
  tg ( x 2 − 3 x + 2 ) x −2
lim 65) lim
63)
x →2
 x −4 
2 64)
x →2 x2 − 4 x →4 (
sen x 2 −16 )
cos (πx ) 1  1  sen x
66) lim 67) lim x sen   68) lim x sen   69) lim
x →1 2 2 x −1 x →∞
x  x →0
x  x →∞ x
70) lim
x →∞
arctg x 71) lim arctg x
x →−∞
72) lim arcsen x
x →∞
x
lim+ (1 + 3 x ) lim (1 + sen x )   1 
1 sen x x
73) 74) 75) lim  1 + sen   
x →0 x →∞  x 
x →0
  
 x +1 
sen x
log ( 3 + h ) − log 3   3 
76) lim   77) lim 78) lim  x log 1 +  
x →0
 x −2  h →0 h x →∞
  x 

79) ( ( ) (
lim log x 2 − 2 x + 6 − log 2 x 2 + 3x − 5 )) 80) lim
(
ln cos 2 x )
x→ ∞ x→0 x2
83)

81) lim
( )
ln 5 + h 2 − ln 5 
 ln
82) lim+  ( x− 3 ) + ln 
 x 

 x 
log 
1 − x 2
 + log 


h →0 h2 x →3
 x −3 
  1 − x   x 
lim+
x →0 3x